Comparing the use of Social Media for Brand and Consumer Engagement at a Local FMCG and a Multinational Corporation in Pakistan - Zafar, Siham (2013)
This paper reports on the results of 50 questionnaires and 6 semi-structured interviews carried out with marketing professionals in two consumer focused companies in Pakistan: Engro Foods Limited and Rocket Internet. Engro Foods Limited is a local FMCG and Rocket Internet is a multinational internet incubator. The purpose of this research is to examine the use of social media as a tool for brand and consumer engagement at the two respective organisations and to compare the social media practices of a local company to that of a multinational. A sequential mixed methods approach was adopted to gather data, using a combination of questionnaires and semi-structured interviews. SPSS was used to analyse the dataset acquired from the questionnaires, while thematic analysis was used to identify themes from the interview transcripts. Findings from the questionnaires indicate that both organisations use social media as a tool for brand and consumer engagement, with Facebook being the most popular medium. The six overarching themes from the thematic analysis of the texts of the interviews highlight a wide range of aspects associated with social media for brand and consumer engagement. The themes examine relevant social media platforms, emerging social media platforms, reach of social media, engagement and interaction, social vs. traditional, paid vs. unpaid, ROI of social media, and future of social media. The themes were discussed in light of the literature, and conclusions were drawn regarding the use of social media for brand and consumer engagement at EFL and Rocket Internet. The paper concludes by drawing implications for marketing professionals and suggesting topics for further research.